Las dimensiones sociales, ambientales y economicas de las reformas a la politica forestal de Bolivia - Contreras Hermosilla, A.; Vargas Rios, M.T. (Forest Trends and CIFOR, 2002)
This paper looks at the experience of designing and implementing policy reforms in the Bolivian forestry sector. It does not attemp to evaluate the process of reform itself but rather to examine the main obstacles faced in its planning and implementation and how the lessons of the Bolivian experience could be transferred to other countries attempting similar changes. Given the drastic nature of reform, it is not surprising that problems along the way were numerous. However, despite difficulties, progress has been significant. This, largerly, was due to a successful alliance between committed Bolivian reformers and a very effective effort by international assistance agencies. Much remains to be done. However, the Bolivian experience shows that a dedicated government can do much to modify the management of the national forest resources.